REVIEW: Twardzisz P. Defining ‘Eastern Europe’: A Semantic Inquiry into Political Terminology. S. l. : Palgrave Macmillan, 2018. XVII, 259 p. - Шмігер, Tарас; Shmiher, Taras (My University, 2018)
REVIEWS Twardzisz P. Defining ‘Eastern Europe’: A Semantic Inquiry into Political Terminology. S. l. : Palgrave Macmillan, 2018. XVII, 259 p.
Keywords: book review; Twardzisz P.; semantic inquiry; political terminology; Eastern Europe; defining